Electroluminescent characteristics of spin-assembled multilayer films with confined layer structure - Kim, Hosub; Cho, Jinhan; Kim, Dong Young; Char, Kookheon (ELSEVIER SCIENCE SA, 2007)
Multilayer films composed of poly(p-phenylene vinylene) (PPV) as the semiconducting polymer and poly(methacrylic acid) (PMAA) as the insulating polymer were fabricated by spin-assembly method. These films, comprising a confined layer structure, showed that the water contact angles are periodically and distinctly oscillated when the top surface layer is alternated between PPV precursor and PMAA. The turn-on voltage of the multilayer electroluminescent (EL) devices increased from 2.6 V to 9.8 V as the thickness of the PMAA layer inserted between neighboring PPV layers was increased from 0 (i.e., PPV single layer film) to 2.0 nm. Furthermore, the emission peaks in the photoluminescent and EL spectra of these devices were strongly blue-shifted due to excitons formed at the confined PPV layers. Particularly when inserting about 1.0 nm thick PMAA layers, which possibly induced a tunneling effect on the charge carriers (i.e., holes and electrons), these multilayer films decreased the mobility of the hole carriers in the PPV layers with strong hole transporting characteristics, and therefore increased the recombination probability in the emitting layer with confined geometry. As a result, the device efficiency was significantly improved in comparison with that of a PPV single layer device without PMAA layer and with that of devices with relatively thick PMAA layers of 1.4 or 2.0 nm. (C) 2007 Elsevier B.V. All rights reserved.